Towards ideal lattice-based cryptography on ASIC : a custom implementation of number theoretic transform - Ho, Truong Phu Truan (2021)
The following topics are dealt with: learning (artificial intelligence); feature extraction; medical signal processing; computational complexity; neural nets; electroencephalography; array signal processing; signal classification; MIMO communication; image classification.